Bilateral temporomandibular joint dislocation following pulmonary function testing: a case report and review of closed reduction techniques. Issue 7 (23rd June 2008) - Oliphant, R; Key, B; Dawson, C; Chung, D
Abstract : Temporomandibular joint (TMJ) dislocation is not a common presentation to the emergency department (ED) but one that requires prompt diagnosis and reduction. This is the first reported case of spontaneous bilateral TMJ dislocation after routine pulmonary function testing. The management of the case is discussed and a review of closed reduction techniques commonly used in the ED is presented.